School-Based Obesity Prevention Intervention in Chilean Children: Effective in Controlling, but not Reducing Obesity - Juliana Kain; Fernando Concha; Lorena Moreno; Bárbara Leyton (Journal of Obesity)
Objective. To evaluate the effectiveness of a 12-month multicomponent obesity prevention intervention. Setting. 9 elementary schools in Santiago, Chile. Subjects. 6–8 y old low-income children (N=1474). Design. Randomized controlled study; 5 intervention/4 control schools. We trained teachers to deliver nutrition contents and improve the quality of PE classes. We determined % healthy snacks brought from home, children’s nutrition knowledge, nutritional status, duration of PE classes, and % time in moderate/vigorous activity (MVA). Effectiveness was determined by comparing Δ BMI Z between intervention and control children using PROCMIXED. Results. % obesity increased in boys from both types of schools and in girls from control schools, while decreasing in girls from intervention schools (all nonsignificant). % class time in MVA declined (24.5–16.2) while remaining unchanged (24.8–23.7%) in classes conducted by untrained and trained teachers, respectively. In boys, BMI Z declined (1.33–1.24) and increased (1.22–1.35) in intervention and control schools, respectively. In girls, BMI Z remained unchanged in intervention schools, while increasing significantly in control schools (0.91–1.06, P=0.024). Interaction group * time was significant for boys (P<0.0001) and girls (P=0.004). Conclusions. This intervention was effective in controlling obesity, but not preventing it. Even though impact was small, results showed that when no intervention is implemented, obesity increases.